Graph Functions in Terms of "Gem-Sets" - Maryam Adnan AL-Ethary; Maryam Sabbeh Al-Rubaie; Maha Khalid Kadhim (Scientific Trends, 2023)
The primary purpose of paper is to define and study a novel type of graph function under the idea of " Gem-Set" named β^*-closed graph , ω^*-closed graph and 〖sem〗^*-closed graph , then we define K^*-map , 〖KO〗^*-map , T^*-map and T^(**)-map , then we are study the properties of it's and the relationships with our function .
Keywords: closed graph functions, K^*-map , 〖KO〗^*-map , J^*-map and J^(**)-map.